CLINICAL COURSE OF RECURRENT APHTHOUS STOMATITIS IN WOMEN OF FERTILE AGE: ETIOLOGICAL FACTORS, SYMPTOMS, AND TREATMENT APPROACHES - Navruzova ugilkhon Orzijon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Etiology and Pathogenesis The pathogenesis of RAS involves a complex interplay of genetic, immunological, and environmental factors. It is believed to be a T-cell mediated immune response against the oral mucosa. Genetic predisposition plays a significant role, with several polymorphisms identified in genes related to immune function, such as TNF-α, IL-1β, and NOD-like receptors In women, hormonal fluctuations, particularly during the menstrual cycle, have been suggested to influence the occurrence of RAS. A study comparing serum levels of sex hormones in women with RAS and healthy controls found significant differences, indicating a potential hormonal influence on RAS development Other contributing factors include nutritional deficiencies (e.g., vitamin B12, iron, folic acid), stress, trauma to the oral mucosa, certain medications, and systemic conditions like celiac disease and inflammatory bowel disease